Epicardial adipose tissue is a robust measure of increased risk of myocardial infarction – a meta-analysis on over 6600 patients and rationale for the EPIC-ACS study. Issue 52 (30th December 2021) - Hendricks, Stefanie; Dykun, Iryna; Balcer, Bastian; Totzeck, Matthias; Rassaf, Tienush; Mahabadi, Amir Abbas
Abstract: Background: Epicardial adipose tissue (EAT) surrounds the heart and the coronary vessels. EAT produces pro- and anti-inflammatory cytokines. Several studies have already documented the association of EAT and cardiovascular risk factors as well as coronary artery disease manifestations. Currently computed tomography (CT) is considered the gold standard for measurement of 3-dimensional volume of EAT. In addition, echocardiography might be an easy accessible alternative in particular in an emergency setting. Methods: We performed a metaanalysis of existing studies describing the differences of EAT in patients with and without myocardial infarction. We used established databases and were searching for "epicardial adipose tissue" or "pericardial adipose tissue" and "myocardial infarction", "coronary events", or "acute coronary syndrome". We included over 6600 patients from 7 studies. Random effect models were calculated and all analyses were performed by using the Review Manager 5.3. Results: Patients with myocardial infarction had 37% (confidence interval [0.21-0.54], P value <.001)] higher measures of EAT compared to patients without myocardial infarction. Comparing studies using echocardiography vs CT for assessment of EAT thickness, similar relative differences in EAT with wide overlap of confidence intervals were observed (for echocardiography: 0.4 [0.04-0.76], for CT: 0.36 [0.16-0.57], P value <.001 for both). Conclusions: Patients with myocardial infarction have more EAT as compared to patients without myocardial infarction independently of the used imaging modality. Further prospective studies are needed to evaluate, how quantification of EAT in clinical routine can improve patients management. Abstract : Supplemental Digital Content is available in the text